LncRNA SNHG17 knockdown promotes Parkin-dependent mitophagy and reduces apoptosis of podocytes through Mst1. Issue 16 (17th August 2020) - Guo, Feng; Wang, Weimin; Song, Yi; Wu, Lina; Wang, Jiao; Zhao, Yanyan; Ma, Xiaojun; Ji, Hongfei; Liu, Yanling; Li, Zhizhen; Qin, Guijun
ABSTRACT: LncRNAs play important roles in the regulation of podocyte apoptosis in diabetic nephropathy (DN). However, the role of lncRNA SNHG17 in controlling mitophagy-induced apoptosis of podocytes in DN is unknown. This study aims to elucidate the underlying mechanism of lncRNA SNHG17 in the regulation of mitophagy-induced apoptosis of podocytes in DN. LncRNA SNHG17 and Mammalian Sterile 20-like kinase 1 (Mst1) expression were upregulated in glomeruli and podocytes of DM mice and high glucose-treated podocytes, whereas Parkin expression was downregulated. LncRNA SNHG17 overexpression suppressed mitophagy and induced apoptosis of podocytes while silencing lncRNA SNHG17 promoted mitophagy and reduced the apoptosis of podocytes. In addition, lncRNA SNHG17 interacted with Mst1 and regulated the degradation of Mst1. We further found lncRNA SNHG17 regulated Parkin expression through Mst1. Mechanistically, lncRNA SNHG17 regulated Parkin-dependent mitophagy and apoptosis of podocytes through regulating Mst1. Finally, silencing lncRNA SNHG17 promoted mitophagy and relieved DN in vivo . In conclusion, lncRNA SNHG17 knockdown promotes Parkin-dependent mitophagy and reduces apoptosis of podocytes through regulating the degradation of Mst1.